Carbon sequestration potential of green roofs using mixed-sewage-sludge substrate in Chengdu World Modern Garden City. (February 2015) - Luo, Hongbing; Liu, Xiaoling; Anderson, Bruce C.; Zhang, Ke; Li, Xiaoting; Huang, Bo; Li, Mei; Mo, You; Fan, Liangqian; Shen, Qiong; Chen, Fenghui; Jiang, Mingshu
Highlights: Sewage sludge mixed local-natural soil was reused as green roof substrates to improve both urban construction and urban ecological environment. MSSS (mixed-sewage-sludge substrate) was found as a promising potential substrate with a high ability of carbon sequestration and carbon storage. Among three native plants, Ligustrum vicaryi was considered as the most suitable plant on green roofs to sequester urban carbon. Carbon sequestration can be considered as an indicator to assess one of the ecological function for green roof. Comparing the discharged urban CO2, best configuration of green roof (MSSS + Ligustrum vicaryi ) was calculated to evaluate future carbon potential, which will effectively mitigate local climate changes in Chengdu World Modern Garden City with great carbon sequestration quantity. Abstract: Green roofs which use sewage sludge to sequestrate urban carbon dioxide may represent a potential opportunity to evaluate carbon sequestration benefits for the urban development under increasing global climate change. In this study, green roofs composed of 6 small green segments with two different substrates, mixed-sewage-sludge substrate (MSSS, volume ratio of sewage sludge and local-natural soil 1:1), and local-natural soil (LNS), three different substrate depths (20 cm, 25 cm and 30 cm), and three types of native plants ( L igustrum vicaryi, Neottia auriculata, and Liriope spicata ) in Chengdu City were established to determine carbon sequestration from July 2012 to July 2013 through assessment of the carbon storage and sequestration. Results show that the average carbon storage of MSSS and LNS on green roofs was respectively 13.15 kg C m −2 and 8.58 kg C m −2, and the average carbon sequestration followed the order of LNS (3.89 kg C m −2 yr −1 ) > MSSS (3.81 kg C m −2 yr −1 ). Thus MSSS could be considered as a potential material for carbon sequestration. The carbon storage and carbon sequestration by native plants on the green roofs followed the order of L. vicaryi > L. spicata > N. auriculata . The whole green roof had a mean carbon storage of 18.28 kg C m −2 and average carbon sequestration of 6.47 kg C m −2 yr −1 in the combined biomass and substrate organic matter. The best green roof configuration was L. vicaryi together with MSSS substrate, with a middle-high level of carbon sequestration. It will be feasible and worthwhile to scale-up the adaptable green roof configurations in Chengdu World Modern Garden City.